Incidence of congenital uterine malformation in fertile female population undergoing laparoscopic tubal ligation at a tertiary care centre, Lucknow, Uttar Pradesh, India: a study of six years - Srivastava, Deepali; Srivastava, Sandeepa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Congenital uterine anomalies are not only uncommon, many are asymptomatic. A uterine malformation is a type of female genital malformation resulting from an abnormal development of the mullerian ducts during embryogenesis. The prevalence of uterine malformation is estimated to be 6.7% in general population. Methods: This study has included 2423 women who attended family planning OPD in KGMU for purpose of laparoscopic tubal ligation along with general and systemic examination. During the laproscopic ligation procedure the observed uterine anomalies were noted and compared to the data available in the existing medical literature. Results: Out of 2423 females included in this study during 2011-2016, 104 (4.29%) females were diagnosed with uterine anomalies. The Commonest uterine anomaly was arcuate uterus which was seen in 77 patients. (3.1%). Uni-cornuate uterus was seen in 19 patients (0.8%) and bi-cornuate uterus was seen in 9 patients (0.3%). 3 out of these were uni-cornuate uterus with rudimentary horn. Conclusions: Though the congenital uterine malformations are frequent findings in infertile patients but few malformations like uni-cornuate uterus, arcuate uterus and bicornuate uterus are although rare but seen in fertile females, showing their lesser impact on pregnancy and its outcome.